2020
DOI: 10.1051/0004-6361/202037884
|View full text |Cite
|
Sign up to set email alerts
|

The First Billion Years project: Finding infant globular clusters at z = 6

Abstract: Aims. We aim to conduct an assessment of the demographics of substructures in cosmological simulations to identify low-mass stellar systems at high redshift, with a particular focus on globular cluster (GC) candidates. Methods. We explored a suite of high-resolution cosmological simulations from the First Billion Years Project (FiBY) at z ≥ 6. All substructures within the simulations have been identified with the SUBFIND algorithm. From our analysis, two distinct groups of objects emerge. We hypothesise that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 142 publications
(132 reference statements)
4
10
0
Order By: Relevance
“…In state-of-the art cosmological hydrodynamic simulations performed at very high resolution (i.e. dark matter particle mass resolution of ∼ 1000 M and, in some cases, pc-scale softening length for baryons, Ma et al 2020), bound and dense clumps in gas-rich highredshift galaxies have been identified, with sizes and masses below 100 pc, consistent with the typical values of star clusters (Kim et al 2018;Phipps et al 2020) and with the values measured in our sample. A systematic comparison between the properties of our clumps and the ones of current state-of-the art simulations is deferred to a future work.…”
Section: Simulationssupporting
confidence: 89%
“…In state-of-the art cosmological hydrodynamic simulations performed at very high resolution (i.e. dark matter particle mass resolution of ∼ 1000 M and, in some cases, pc-scale softening length for baryons, Ma et al 2020), bound and dense clumps in gas-rich highredshift galaxies have been identified, with sizes and masses below 100 pc, consistent with the typical values of star clusters (Kim et al 2018;Phipps et al 2020) and with the values measured in our sample. A systematic comparison between the properties of our clumps and the ones of current state-of-the art simulations is deferred to a future work.…”
Section: Simulationssupporting
confidence: 89%
“…At least in part motivated by the impending launch of JWST (and facilitated by technical improvements in hardware and modelling), a wide variety of recent studies has made predictions of the properties of young GC populations at high redshift. These range from back-of-the-envelope estimates, assuming simple scaling relations (e.g., Katz and Ricotti 2013;Renzini 2017;Boylan-Kolchin 2018), to expectations based on observations of nearby GC populations (e.g., Zick et al 2018) and high-redshift star formation (e.g., Vanzella et al 2017), and predictions from numerical simulations of galaxy formation, either by 'painting on' GCs using an ad-hoc model (e.g., Renaud et al 2017;Halbesma et al 2019;Madau et al 2019;Phipps et al 2019) or by including a physical description for GC formation and evolution (e.g., ). The resulting predictions for when GCs formed and what their corresponding detectability is with future observations with JWST or 30-m class telescopes vary greatly between these different approaches.…”
Section: Current and Future Observations And Simulations Of Massive Cluster Formation Across Cosmic Timementioning
confidence: 99%
“…2 The first category of models takes a 'normal' galaxy formation simulation and uses some set of conditions (e.g. cuts in age, metallicity, or halo mass) to associate GCs to star particles (e.g., Renaud et al 2017;Halbesma et al 2019;Madau et al 2019;Phipps et al 2019). This 'particle tagging' technique has had difficulties to reproduce the observed demographics of GCs, such as their total number per unit galaxy mass and their age or metallicity distribution.…”
Section: Current and Future Observations And Simulations Of Massive Cluster Formation Across Cosmic Timementioning
confidence: 99%
“…Simulations also place BH growth in its full astrophysical context against the backdrop of dark matter driven galaxy formation. Simulations have shown that the energy released from the accretion process has the capacity to impact a wide range of spatial scales -from the smallest scales where general relativity and magneto-hydrodynamic processes dominate to the largest scales wherein outflows driven by accreting black holes and their feedback are relevant (Beskin and Kuznetsova, 2000;Komissarov, 2001;Gammie et al, 2003;Komissarov, 2005;McKinney, 2005;Harrison et al, 2018;Phipps et al, 2020). This coupling of scales might hold the key to understanding the observed correlations.…”
Section: Simulated Datamentioning
confidence: 99%